2023
DOI: 10.1002/jsfa.12707
|View full text |Cite
|
Sign up to set email alerts
|

Changes in, and correlation analysis of, volatile compounds, key enzymes, and fatty acids in lemon juice vesicles during freeze drying and hot‐air drying

Abstract: BACKGROUNDLemon juice vesicles are distinguished by their unique and abundant volatile flavor compounds, which can undergo complex changes during drying. In this study, integrated freeze drying (IFD), conventional freeze drying (CFD), and hot‐air drying (AD) were used to dry lemon juice vesicles to investigate the changes in, and correlations among volatile compounds, fatty acids, and key enzyme activity during the drying process.RESULTSTwenty‐two volatile compounds were detected during the drying processes. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Freeze drying retains more fatty acids in fruits compared to air drying. A study on lemon juice vesicles reported a loss of 67.68% in total fatty acids after air drying, 53.00% in conventional freeze drying and 36.95% in integrated freeze drying [ 53 ]. Additionally, most fatty acid levels increased with increasing PEF intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Freeze drying retains more fatty acids in fruits compared to air drying. A study on lemon juice vesicles reported a loss of 67.68% in total fatty acids after air drying, 53.00% in conventional freeze drying and 36.95% in integrated freeze drying [ 53 ]. Additionally, most fatty acid levels increased with increasing PEF intensity.…”
Section: Resultsmentioning
confidence: 99%
“…For hydrocarbons, more alkanes and olefins were detected in all three samples, and the response intensity of alkanes in the vacuum freeze-dried samples was higher, which may be due to the fact that with the loss of water in the samples, the volatile flavor components of olefins changed under the low-temperature and vacuum conditions, and the spatial structure changed [53], resulting in the generation of a variety of alkanes. The flavor threshold of hydrocarbons is generally high and has little effect on the overall flavor change of raw materials.…”
Section: Effects Of Different Drying Methods On the Volatile Substanc...mentioning
confidence: 93%